Validity of ESD-Oriented E-LKPD Using Liveworksheets to Improve Environmental Literacy of Elementary School Students - Nadiah; Suratmi (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
The low level of environmental literacy among elementary school students indicates the need to develop contextualized and ESD-oriented teaching materials. However, the integration of ESD content in science learning at the elementary school level remains limited. This study aims to test the validity of ESD-oriented E-LKPD developed using Liveworksheets platform to improve students’ environmental literacy. This quantitative descriptive research focuses on the expert validation process. and forms part of a larger development process using the 4D model (Define, Design, Develop, Disseminate), which is limited to the develop stage. Validation was conducted by material and media experts using validation sheet instruments. The results showed that the E-LKPD obtained an average score of 96.88% from material experts and 96.25% from media experts, with a very valid category. Follow-up in the form of minor revisions was made to improve content accuracy, instructions, and interactive features of the media. These results indicate that the developed E-LKPD is feasible to use in science learning and has the potential to improve students' environmental literacy. This research contributes to the development of ESD-based interactive digital media at the elementary level, and lays the groundwork for testing the effectiveness of the product at a later stage.